Genotype prevalence and allele frequencies of 5,10-methylenetetrahydrofolate reductase (MTHFR) C677T mutation in two caste groups of India - Rai, V.; Yadav, U.; Kumar, P. (Cellular and Molecular Biology, 2012)
The aim of the present study was to investigate the distribution of 5,10-methylenetetrahydrofolate reductase (MTHFR) polymorphism in two caste group populations of eastern Uttar Pradesh. This mutation has been suggested to be positively associated with the risk of several congenital and multifactorial disorders. Frequency of mutant T allele differs in various ethnic and geographical populations of the world. MTHFR C677T mutation analysis was carried out by PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) method and the samples studied were randomly selected from the healthy individuals belonging to two caste populations. In Brahmin samples, genotype frequencies of CC, CT and TT were 0.727, 0.25 and 0.023 respectively whereas in Rajput samples, CC genotype was observed in 88 samples, CT genotype in 25 and TT genotype was found in 2 samples. Frequency of mutant T allele was found to be 0.147 in Brahmin and 0.126 in Rajput populations. The percentage of CT genotype and C allele were high in both the populations.